Evaluations in the Moodle-Mediated Music Teaching-Learning Environment - Espigares Pinazo, Manuel Jesús; Bautista Vallejo, José Manuel; García-Carmona, M. (Springer, 2022)
This study presents the use of automated data analysis procedures in the teaching-learning process, mediated by telematics platforms. It is based on the application of the principles of virtual learning, the use of the Internet and the automation of data analysis of information collected in Moodle. The application of analysis procedures for the assessment of music competences is proposed based on the data collected in an exam administered at the end of the course. The sample of the study consists of 1327 students (n = 1327) in the first year of Compulsory Secondary Education in Spain and measures the level of acquisition of the key competences denominated “cultural and artistic”. The results are subjected to the K-means classification technique. This technique is used to obtain homogeneously distributed conglomerates which allow for an objective evaluation of the levels of acquisition of the key musical competences. © 2020, Springer Nature B.V.
Keywords: assessment; educational software; free software; ICT; music education; telematics resources; Scopus; Emerging